A Systematic Approach to the Development and Synthesis of Multi-nuclear Complexes Possessing Novel Magnetic Behaviour - Pathmalingam, Thushan (University of Ottawa (Canada), 2010)
The chapters in this thesis are sequentially arranged In increasing nuclearity and atomic configuration (i.e. linear Mn3, triangular Mn3, Mn6, Mn7, Mn9, Mn18, and Mn23). In order to synthesize these molecules tuneable, multi-dentate oximate ligands were employed. These compounds were characterized exclusively by X-ray crystallography and their magnetic properties by SQUID measurements. The latter permits us to determine the spin ground state and the magnetic anisotropy and hence ultimately establish whether the molecules exhibit the single-molecule magnet (SMM) behaviour. In addition to the atomic structure, a magneto-structural correlation was conducted for the 21 manganese clusters. In an attempt to achieve high energy barrier SMMs two essential requirements; large spin ground state and uniaxial magnetic anisotropy were manipulated. Each chapter was discussed in regards to achieving SMM behaviour by tweaking one or both requirements. There are two basic magnetic repeating units which lay the foundation for large Mn aggregates; linear Mn 3 and triangular Mn3. The former can be used to produce linear 1-D chains of Mn3 polymer. The latter can be used to synthesize Mn6, Mn7, Mn9, Mn18 and Mn 23 clusters.* *Please refer to dissertation for diagrams.
Keywords: Chemistry, Molecular.